PENGUATAN KAPASITAS POKJA DESA DAMAI DALAM MEMBANGUN SISTEM DETEKSI DINI KEKERASAN BERBASIS GENDER DI TINGKAT DESA - Ahmad Ainun, Najib; Halimatus Sa’diah; Nurin Baroroh; Ahmad Syamsul Mua’rif (IJTIMA': JURNAL PENGABDIAN MASYARAKAT, 2026)
Gender-based violence remains a persistent social problem at the village community level and is often undetected in its early stages due to limited public awareness, inadequate reporting mechanisms, and the weak capacity of local institutions to respond to such cases. This condition encouraged the implementation of a community service program aimed at assisting the Peace Village Working Group (Pokja Desa Damai) in developing an early detection system for gender-based violence in Grajagan and Barurejo Villages, Banyuwangi. The program was designed to enhance the capacity of working group members to identify signs of violence, provide initial responses, deliver basic psychological support, and establish responsive reporting and referral mechanisms at the village level. The methods employed included Training of Trainers (TOT), interactive lectures, brainstorming sessions, role-playing, case simulations, and collaborative action plan development. The main materials covered Psychological First Aid, violence prevention and response strategies, basic counseling techniques, and community-based early detection system development. The results indicated an increase in participants’ understanding of the forms and impacts of gender-based violence, improved basic counseling and victim assistance skills, the strengthening of the Peace Village Working Group’s commitment as a community support center, and the formulation of socialization plans and communication channels for reporting cases within the villages. This program demonstrates that community-based assistance can effectively strengthen village preparedness in preventing and addressing gender-based violence through participatory and sustainable approaches.